Quality assessment of domestic harvested rainwater in the peri-urban region of Kleinmond, Western Cape and the optimisation of point-of-use treatment systems - Dobrowsky, Penelope Heather (Stellenbosch : Stellenbosch University, 2014)
Thesis (MSc)--Stellenbosch University, 2014.